Pelatihan Literasi Digital Dalam Bermedia Sosial Pada Ikatan Remaja Islam Masjid At-Taubah - Muhamad Hasan; Jordy Lasmana Putra; Mugi Raharjo; Hani Harafani (Jurnal AbdiMas Nusa Mandiri, 2022)
The At-Taubah Mosque Islamic Youth Association (IKRIMA) is an Islamic mosque organization located in the Pancoran area, South Jakarta. The various activities they carry out now include the use of the internet and of course social media as a means of seeking and obtaining information. Social media is something that internet users access the most every day. However, as we know Social Media has two sides, namely positive vibes and negative vibes where it all comes back to each of us in responding to or creating the content. For that we need positive content that is educational in nature so that we can balance the negative side of other content. Not all IKRIMA members are aware that social media actually contains information, identity, and digital traces in it. Currently, social media is still used to only express feelings, sadness, joy, confusion, longing to be poured out there. Therefore, it is necessary to hold counseling in the form of community service activities to fulfill the Tridharma of Higher Education with the aim of providing insight to the At-Taubah Mosque Islamic Youth Association regarding the importance of knowing Digital Information, Digital Identity, and Digital Footprints contained in a Social Media. With the hope, the administrators and members of the Islamic Youth Association of Masjid At-Taubah (IKRIMA) can understand the importance of this in daily activities which incidentally always refers to social media and is wise in using it so that negative things don't happen that we don't want.